Pembangunan Desa Berkelanjutan Melalui Partisipasi Masyarakat: Studi Kasus Pengabdian di Desa Catak Gayam - Wahib, Moh.; Stafrezar, Burhan; Susanto, Ari (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2024)
This article discusses sustainable village development efforts through a community participation approach in Catak Gayam Village. This service project is designed to improve the welfare of village communities by actively involving them in every stage of development, from identifying needs to project implementation. Through observation, survey and training methods, the Catak Gayam Village community is empowered to play an active role in decision making and managing local resources. The results of this project show a significant increase in the quality of village infrastructure as well as community capacity to manage development sustainably. Community participation proved to be a key factor in the success of this project, creating a strong sense of ownership and responsibility for development outcomes. These findings provide an important contribution to village development models that can be applied in other regions with similar conditions.